(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to determine the relationship between coping strategies and stress in the workers of the Food Company "ARSAICO" of the Canton Chambo - Ecuador. The study population is 20 workers that is the entire company, sociodemographic variables are considered for the study, this research is quantitative approach, descriptive type with non-experimental correlational and cross-sectional design. The tests applied were the COPE questionnaire for coping and WHO - ILO for stress. For the information processing, the statistical program SPSS version 24 and the Spearman correlation coefficient were used, finding a significant inverse relationship between stress and coping. Regarding the analysis between before and after the program, positive psychology decreases stress levels from medium to low with high coping.